2004
DOI: 10.1158/1078-0432.ccr-1026-3
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Expression of Interleukin-18 and Its Receptor in B-Cell Lymphoproliferative Disorders Deriving from Naive, Germinal Center, and Memory B Lymphocytes

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 48 publications
2
27
1
2
Order By: Relevance
“…Although the contribution of IL-1a/b and IL-18 in lung Th2 responses has been interpreted as an adjuvant effect through epithelial cells and APCs or a direct effect on CD4 + T cells, the role of these cytokines in B cells was previously unknown. However, recapitulating our results from this study and the fact that functional IL-1R and IL-18R are expressed on B cells (54)(55)(56), IL-1a/b and IL-18 also stimulate B cells to promote GC responses and IgE/IgG1 production during the airway instillation of pollen allergens. The results demonstrated in this study are not contradictive to the roles for IL-1 family cytokines on epithelia, myeloid APCs, or T cells that were described previously (37)(38)(39)(40).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although the contribution of IL-1a/b and IL-18 in lung Th2 responses has been interpreted as an adjuvant effect through epithelial cells and APCs or a direct effect on CD4 + T cells, the role of these cytokines in B cells was previously unknown. However, recapitulating our results from this study and the fact that functional IL-1R and IL-18R are expressed on B cells (54)(55)(56), IL-1a/b and IL-18 also stimulate B cells to promote GC responses and IgE/IgG1 production during the airway instillation of pollen allergens. The results demonstrated in this study are not contradictive to the roles for IL-1 family cytokines on epithelia, myeloid APCs, or T cells that were described previously (37)(38)(39)(40).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the administration of IL-18 induced strong GC responses and the production of IgE (54). In humans, IL-18Ra is expressed on GC and memory B cells at higher levels than on naive B cells (55), suggesting involvement of IL-18 in GC Ab production. These studies demonstrate that direct stimulation of B cells by IL-18 can enhance the GC response and IgE production.…”
Section: Discussionmentioning
confidence: 98%
“…[21][22][23] It has been reported that IL-18 is localized in the dermis in the auricle at 24 hr after the elicitation of CHS with OXA. 34) Our result shows that IL-18 is also localized in the dermis before the elicitation of CHS (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] IL-12 and IL-18 are produced by professional antigen presenting cells, 20) as well as lymphocytes. [21][22][23] The effect of E2 on these chemokines and cytokines has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…IL-18 and CA125 have comparable diagnostic potential. However, since IL-18 has also been observed in patients with squamous cell carcinoma, 39 myeloma, 40 endometriosis and endometrial cancer 41 and T-cell leukemia, 42 it is clear that IL-18 alone cannot be used as a specific marker of ovarian cancer. Although CA125 remains the best individual marker, the combination of CA125, IL-18 and FGF-2 is superior in specificity than using CA125 alone in ovarian cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%